Електрографічний та цифровий друк: класифікаційні ознаки - Григор’єв, О. В.; Вовк, О. В.; Росинська, К. А.; Майборода, Д. А. (ТОВ «Видавництво Ліра-К», 2025)
A general classification of electrographic printing equipment according to various technical and technological characteristics is given, which allows, if necessary, to make recommendations on the appropriateness of using this equipment to solve certain tasks in the production of various types of printing products.
Keywords: електрографічний друк; цифровий друк